2018
DOI: 10.3390/nu10020218
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Home Food Consumers in Brazil: What do They Eat?

Abstract: Considering the increased contribution of foods consumed outside home and their potential impact on diet, this study aims to identify eating out patterns and their association with nutritional dietary quality in Brazil. We used the Individual Food Intake Survey 2008–2009, conducted with 34,003 individuals aged 10 and up. We used factor analysis by principal component to identify out-of-home eating patterns and linear regression to explore the association between patterns scores and dietary quality. We identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
39
1
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 36 publications
11
39
1
14
Order By: Relevance
“…However, such limitations are mitigated by detailing all deliberations [51]. It is noteworthy that the dietary patterns detected in this study were comparable with those of other studies, which validates the results obtained externally [27,30,34,[41][42][43].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…However, such limitations are mitigated by detailing all deliberations [51]. It is noteworthy that the dietary patterns detected in this study were comparable with those of other studies, which validates the results obtained externally [27,30,34,[41][42][43].…”
Section: Discussionsupporting
confidence: 89%
“…As in the present study, Andrade et al (2018) [27], in a survey of 34,003 individuals from the 2008/2009 Household Budget Survey (POF), showed three dietary patterns in the Brazilian population, with traditional meals, "typical Brazilian breakfast/tea" and the last one with "ultra-processed foods". Nogueira et al (2019) [34], in a study with metallurgists from Fortaleza/CE, Brazil, also identified three eating patterns: the first common northeastern, the second popular general and the third western.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Os alimentos e bebidas consumidos foram categorizados de acordo com o grau e o propósito de processamento, por meio da classificação NOVA, que divide os alimentos em quatro categorias: in natura e minimamente processados, ingredientes culinários, processados e ultraprocessados Devido ao fato de que os alimentos são consumidos em parte na forma de preparações culinárias, para a avaliação do consumo alimentar individual foi realizada classificação dos alimentos e bebidas de acordo com a proposta de Andrade et al (2018), que dividiu os itens ingeridos em três grupos: preparações culinárias, alimentos processados e alimentos ultraprocessados. Para a categorização do grupo de preparações culinárias, os alimentos in natura e minimamente processados foram agrupados com o grupo dos ingredientes culinários.…”
Section: Definição Dos Indicadores Do Consumo De Eventos Alimentaresunclassified